Cubic structured SrTiO3 with Ce/Cr Co-doping for photoinduced catalytic oxidation of gaseous mercury. (May 2022) - Cai, Jun; Ren, Yuanhang; Xia, Yi; Tao, Lei; Wang, Xueqian; Wang, Langlang; Ning, Ping; Ma, Yixing
Abstract: A cubic SrTiO3 (STO) composite material co-doped with Ce and Cr ions was synthesized by solvothermal method. The fully characterized samples were employed as photocatalysts for the oxidation of Hg 0 . The co-doped samples afforded excellent catalytic removal efficiency of 98.99% using UV irradiation and 89.9% using visible light irradiation for Hg 0 compared with the single-doped samples. It was found that co-doped samples had a lower electron-hole recombination rate, largest Brunauer-Emmett-Teller specific surface area, and reduced band gap. The electron spin resonance results revealed that ·O2 − and ·OH were the main active species in the catalytic process. Moreover, the co-doped samples exhibited the best electron transfer rate and the highest photocurrent response intensity. The electron transfer between the elements in the co-doped sample enables it to achieve stable and efficient catalytic performance. In addition, even after five consecutive catalytic runs, the co-doped sample maintained high catalytic activity. This work highlights the potential of the perovskite-type STO materials in the photocatalytic oxidation of gaseous mercury. Graphical abstract: Proposed mechanism for the photocatalysis on Sr0.9 Ce0.1 Ti0.9 Cr0.1 O3 . Image 1 Highlights: Successful synthesis of Ce and Cr co-doped SrTiO3 cubic catalyst. The introduction of Ce and Cr in SrTiO3 reduced the band gap. O2 − and ·OH are the main active radicals in the photocatalytic oxidation of Hg 0 . The mechanism of the photocatalytic removal of Hg 0 has been proposed.